E-281 A multicenter study evaluating access site and bad score categorization in reperfusion timing and outcomes in anterior circulation acute ischemic large vessel occlusions undergoing mechanical thrombectomy. (23rd July 2022) - Catapano, J; Koester, S; Naik, A; Stonnington, H; Rangel, I; Winkler, E; Srinivasan, V; Desai, S; Ducruet, A; Albuquerque, F; Jadhav, A
Abstract : Introduction: Given the multifactorial nature of stroke outcomes, recent efforts have been made to better predict time to reperfusion and improved patient outcomes. In previous studies, the B.A.D. score - consisting of bovine arch, aortic arch, and internal carotid artery dolichoarteriopathy categorization - has been shown to be a predictor of prolonged time to reperfusion as well as functional outcome for patients with transfemoral access. We aimed to assess this grading system with consideration to transfemoral versus transradial access. Methods: We retrospectively compared transradial versus transfemoral access for acute anterior circulation ischemic stroke requiring mechanical thrombectomy at two high-volume comprehensive stroke centers. Local institutional review board approval was obtained prior to analysis. Bovine arch, aortic arch, and internal carotid artery dolichoarteriopathy categorization was made for every patient, with higher B.A.D. scores defined as a score of 2 or greater. The primary outcome was change in NIHSS grading from admission to discharge as well as at 24 hours post-thrombectomy. Procedural timing analysis included analysis of time from puncture to first pass and reperfusion. Patients requiring crossover between access sites and tandem occlusions were excluded. Univariate analysis used Wilcoxon rank-sum test for continuous outcomes, while chi-square test and Fisher's exact test were used for categorical comparisons. Significance was defined as p < 0.05. Results: A total of 220 patients were included in the analysis, 161 (73.2%) of which had femoral access. Demographic comparisons and patient presentation did not vary between patients with femoral vs. radial access. Additionally, access site did not show significant difference in B.A.D. scores. The femoral approach had a significantly greater proportion of ASPECT scores less than 9 (39% vs 19%, p = 0.017). A low B.A.D. score was associated with a significantly greater reduction in NIHSS scores from admission to discharge in transfemoral patients (-8 (SD: 8) vs -4 (SD: 7), p = 0.030), however this association was not observed in the transradial patients. No other primary endpoints, including functional outcomes and reperfusion time, showed significant differences in transradial versus transfemoral access or low versus high B.A.D. scores. Conclusion: Our analysis evaluates the prognostic value of the B.A.D. score in the context of varying access sites in predicting outcomes and revascularization time. In contrast to previously published findings in smaller patient cohorts, we demonstrate that B.A.D. score categorization did not show a major association with changes in patient outcomes as well as timing of revascularization. Future research should utilize larger patient samples to enhance preoperative anatomic evaluation models for major stroke outcomes and improve treatment guidance. Disclosures: J. Catapano: None. S. Koester: None. A. Naik: None. H. Stonnington: None. I. Rangel: None. E. Winkler: None. V. Srinivasan: None. S. Desai: None. A. Ducruet: None. F. Albuquerque: None. A. Jadhav: None.